Cambridge Checkpoint English Workbook 7 - Marian Cox (India Replika press ltd, 2012)
The Cambridge Checkpoint English suite provides a comprehensive, structured resource which covers the Secondary 1 framework for English and seamlessly progresses into the next key stage (covered by our Cambridge IGCSE(r) First Language English series). This skill-building, write-in Workbook for Stage 7 is designed to support students' learning and provides extra language tasks and reading and writing skills developmen
Keywords: IGCSE - English + MYP Student Resource MYP Language and Literature -- IGCSE - English + MYP Student Resource MYP Language and Literature